Migración femenina internacional en la frontera sur de México - Ángeles-Cruz, Hugo Manuel; Rojas-Wiesner, Martha Luz (Papeles de Población, 2022)
In the last years, the female migration in Latin America has increase the internal and international movements of women that are searching for better living conditions for themselves and their families. At the southern boarder of Mexico you can identify the costal region and boarder limits of Chiapas with Guatemala as the more dynamic zone in commercial relations and the movement of population between Mexico and its neighbours of Central America, in such conditions is produced different flows of migration to and through this border region. The majority of immigrants use this mechanism to cross the border as the principal destiny to the territory of the United States. However, there exist important immigration flows with the temporary destination to the Soconusco region in mexican territory.